Small Cities in the Development Policy of Warminsko-Mazurskie Voivodeship - Walendzik, Emil; Wojarska, Magdalena; Jett, Quintus (Olsztyn Economic Journal, 2018)
The article focuses on indicating the interpenetration of the development policy of the Warminsko-Mazurskie voivodeship and the development policy of small cities situated in the region. It aims to identify the development opportunities of small cities, within the context of voivodship development policy, and to assess the use of opportunities from this regional level of governance and administration. The study was based on the results of a survey conducted among representatives of urban gminas and urban-rural gminas as well as analysis of strategic and operational documents developed at the regional level. Development problems of small cities in the Warminsko-Mazurskie Voivodeship, identified from the local and regional levels, are very similar. However the differences are visible in terms of the effects of the expected intervention. In the regional documents – both strategic and operational ones, there is no special recognition of issues related to the development of small cities, but they can be found indirectly in some preferences that small towns have in applying for funds from the Regional Operational Program. Unfortunately, not all cities benefit from the opportunities offered by this Program.